Aspergillus terreus as an industrial filamentous fungus for pharmaceutical biotechnology. (June 2021) - Huang, Xuenian; Men, Ping; Tang, Shen; Lu, Xuefeng
Graphical abstract: Highlights: Aspergillus terreus is a valuable filamentous fungus with excellent synthetic capacity for natural products. A number of new secondary metabolites with pharmaceutical potential have been discovered by genome mining. A. terreus has been applied in the industrial production of itaconic acid and lovastatin. Abstract : Aspergillus terreus is an important Aspergillus species, which has been applied in the industrial production of the bio-based chemical itaconic acid and the lipid-lowering drug lovastatin. The excellent fermentation capability has been demonstrated in these industrial applications. The genomic information revealed that the outstanding capacity of natural product synthesis by A. terreus remains to be further explored. With advances of the genome mining strategy, the products of several cryptic biosynthetic gene clusters have been discovered recently. In addition, a series of metabolic engineering studies have been performed in the industrial strains of lovastatin and itaconic acid to further improve the production processes. This review presents the current progress and the future outlook in the field of A. terreus biotechnology.